2017
DOI: 10.1111/joss.12249
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and sensory profiling by children and teenagers: A case study of the check‐all‐that‐apply method on biscuits

Abstract: Sensory and emotional profiling by consumers is gathering interest among scientists and companies as it could help to better understand the motives for food choice. Although children and teenagers are important food consumer groups, they are underrepresented in sensory research and little is known on how children and teenagers perform on these tasks. Therefore, this study investigates the emotional and sensory profiling of a traditional biscuit product among 122 children and teenagers (10–14 years old). The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…This indicates that the CATA method is able to provide more information on which sensory attributes were perceived by a child population to be different from equally‐liked samples, providing more information regarding their drivers of liking (Laureati et al, ). These findings are in line with those reported by Schouteten, De Steur, et al () who examined the possibility of using the CATA response format to obtain discriminatory sensory profiles for speculoos biscuits with a child and teenage population. Furthermore, studies working with children and teenagers showed that the CATA response format is able to obtain distinguished sensory profiles for powdered fruit‐flavored juices (Cardinal et al, ), milk desserts (Vidal et al, ), fiber‐enriched apple purees (Laureati et al, ), and grape nectar (Lima, Ares, & Deliza, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This indicates that the CATA method is able to provide more information on which sensory attributes were perceived by a child population to be different from equally‐liked samples, providing more information regarding their drivers of liking (Laureati et al, ). These findings are in line with those reported by Schouteten, De Steur, et al () who examined the possibility of using the CATA response format to obtain discriminatory sensory profiles for speculoos biscuits with a child and teenage population. Furthermore, studies working with children and teenagers showed that the CATA response format is able to obtain distinguished sensory profiles for powdered fruit‐flavored juices (Cardinal et al, ), milk desserts (Vidal et al, ), fiber‐enriched apple purees (Laureati et al, ), and grape nectar (Lima, Ares, & Deliza, ).…”
Section: Discussionsupporting
confidence: 91%
“…Participants conducted the sensory profiling task by checking all of the sensory terms that they found applicable for the evaluated sample. Fourteen terms, covering different sensory modalities (appearance, aroma, flavor, and texture) were included for the sensory profiling task: “brown color,” “hard,” “herbal aroma,” “buttery aroma,” “granular,” “cinnamon aroma,” “rough surface,” “cinnamon flavor,” “aftertaste,” “strong flavor,” “herbal flavor,” “dry,” “crunchy,” and “soft.” These terms were selected using the results of a pilot study (20 children, aged 11–13 years old) following a two‐step procedure (Schouteten, De Steur, et al, ). In the first step, children individually evaluated the applicability of 30 sensory terms (based on prior research; Schouteten, De Steur, et al, ), to describe the sensory properties of speculoos samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results that compare the sensory perception of different products in blind and informed tests showed that consumers are normally more aware of products when they obtain information about them (Grasso, Monahan, Hutchings, & Brunton, ; Reis, Alcaire, Deliza, & Ares, ; Schouteten, De Steur, Lagast, De Pelsmaeker, & Gellynck, ), especially when these products provide nutritional/health benefits (Grasso et al, ; Reis et al, ). However, to the best of our knowledge, no studies have been published so far evaluating if receiving correct information about a product can override the prejudgments consumers have about processed foods.…”
Section: Introductionmentioning
confidence: 99%
“…In the blind condition, differences in liking scores were motivated by to the type of product: samples with a high percentage of cocoa were less preferred by consumers. Schouteten et al (2017) investigated the brand information impact on children´s overall liking of biscuits. They realized that brand influenced the informed liking scores.…”
Section: Introductionmentioning
confidence: 99%